FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI LADA PUTIH DI DESA TELANAI KECAMATAN BANDING AGUNG KABUPATEN OGAN KOMERING ULU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
This study aims to analyze the factors - factors that affect White Pepper Production in the Village District of Appeal Telanai Ogan Ulu Ogan. The method used in this research is survey method and sampling method used in the study were randomized method (simple random sampling). Based on the analysis, there are three variables that real effect on the production of white pepper that land, seed, labor, while fertilizer prices are not real effect. The land area significantly at the level of 0.40 per cents with a significant value of 0.004, Seeds real effect on the level of 0.2 per cent with significant value 0.002 and fertilizer are also significant factors at the level of 0.10 per cents with significant value 0,000. While the labor factor and the price did not affect the production of white pepper with a significant value of 0.497 and 0.176. The factors that influence the production of white pepper that land, seed, fertilizer, while the labor factor and the price no real effect on the production of white pepper in the village Telanai District of South OKU District Court of Appeal.